Brazilian Olympic female athletes´multidisciplinary care: an observational study - Parmigiano Moreno, T. R.; Poli de Araujo, M.; Cardoso Benayon, P.; Faroni, R. P.; Galindo Novoa Barsottini, C.; Gracio Ferreira Sartori, M. (Revista Brasileira de Medicina do Esporte, 2022)
Introduction: Female participation in sports had reached a milestone in 1972 when a constitutional amendment was implemented to ensure equal opportunities for men and women. Since then, the percentage of participants in competitive sports has grown. In 1992, an association was made between three disorders related to female athletes called the "Female Athlete Triad". After that, much has been studied about this and other particularities of female athletes.